Ocular toxocariasis caused by toxocara canis in an adult woman. Case report - German Santiago Barahona Botache; Mario Javier Olivera (Case Reports)
Introduction: Toxocariasis is a zoonosis caused by the Toxocara canis and Toxocara cati nematodes larvae. These are intestinal parasites found in canids and felids, respectively.